A Study on the Effect of Commuting Distance on the Organizational Commitment - Ali , Siti Aissah Binti Mad; Sorooshian, Shahryar (Journal of Management and Science, 2013)
Urbanization has led to a high rate of necessity to commute nowadays. Regardless of the other factors, sometimes employees have no choice but to commute to work. The aim of this paper is to study on how does the commuting distance affects the organizational commitment of an employee; whether it is the continuance, normative of affective commitment is affected.